Acute myeloid leukemia in SRP54‐mutated congenital neutropenia. Issue 2 (16th March 2022) - Sabulski, Anthony; Grier, David D.; Myers, Kasiani C.; Davies, Stella M.; Rubinstein, Jeremy D.
Abstract: SRP54 mutations have recently been implicated in congenital neutropenia (CN) and the in‐frame deletion, p.Thr117del, is the most common pathogenic mutation reported. The largest study of SRP54 ‐mutated CN to‐date followed 23 patients for a median of 15 years. No patients developed a hematologic malignancy in that study. Given the known risk of leukemia in other CNs it is crucial to know whether patients with SRP54 ‐mutated CN have an increased risk of leukemia. We report the first case of leukemia in a patient with SRP54 ‐mutated CN. A 15‐year‐old male with SRP54 ‐mutated CN (p.Thr117del) was diagnosed with acute myeloid leukemia with myelodysplasia‐related changes on a screening bone marrow evaluation. Next generation sequencing of the leukemia cells identified CSF3R and RUNX1 mutations. These mutations commonly co‐exist in CN‐associated malignancies and suggest leukemogenesis in SRP54 ‐mutated CN may occur in a similar manner to other CNs. He was successfully treated with CPX‐351 followed by hematopoietic cell transplant (HCT) and remains in remission at a follow‐up time of 9 months. Although conclusions from this single report must be limited, this has potentially significant implications for both screening and treatment practices for these patients, including the role and timing of HCT.